Walking with the illness and life: Experience of the community life of people previously under the services of an integrated community mental health service. Issue 6 (20th April 2020) - Chiang, Vico Chung Lim; Chien, Wai Tong; Wan, Ming Chi; Cheung, Sally Yuen Ha
Accessible summary: What is known on the subject?: There have been some studies on the experience and community life of mental health clients receiving integrated community mental health service (ICMHS). Evaluation of ICMHS suggests that the service could have positive clinical and social outcomes, but the results are inconclusive. What does the paper add to existing knowledge?: Research studies have focused on clients and/or staff of the ICMHS, while in this study, the experiences and perspectives of family members are also explored. More comprehensive knowledge about the work for, and community life of, people previously under the services of ICMHS is added to the existing knowledge. This study found that with "timely support" and "family presence, " people who had received the services of ICMHS continued to engage in more social activities ("expanding social networks"), had "better family relationships, " were "letting go" of thinking too much and more able to relax, and had "better self‐efficacy and self‐caring" in the community. Professional contact after ICMHS through continuous conversations (e.g. home visits and follow‐up calls) and social activities are essential for both clients and their families to carry on living with the illness. Timely support, family presence, support to family members in the community and better social networks are key experiences of ICMHS clients. What are the implications for practice?: Although the ICMHS' resources are limited, better promotion is urgently needed for the public to realize the services and to support mental health clients. Mental health professionals may develop practice models through exploratory and confirmatory factors analyses of the themes identified from this study as the outcome measures. The cost‐effectiveness of services and relapse rates over time should also be evaluated for future practice development. Further studies for practice on the difference that family support can make to the community life of former ICMHS clients are warranted. This may be achieved through research designs that compare people with, and without, family members. Abstract: Introduction: More comprehensive understanding, from the experiences and multiple perspectives of the clients, families and staff, about the community life of former clients of the integrated community mental health service (ICMHS) is scarce. Aim: To explore the community life experiences of people after their discharge from the ICMHS. Method: A qualitative approach with an interpretative phenomenological analysis was utilized for this study. Data were collected through individual semi‐structured interviews of 37 participants, including people discharged from an Integrated Community Centre of Mental Wellness, their family members and staff members. Results: Six themes emerged from the analysis: "timely support, " "family presence, " "better family relationships, " "expanding social networks, " "letting go" and "better self‐efficacy and self‐care, " under the main theme of "walking with the illness and life." Discussion: Over and after the ICHMS, with timely support and family presence, there was a positive trend in the experiences of clients in expanding social networks, having better family relationships, letting go of thinking too much and being more able to relax, and improving self‐efficacy and self‐caring. Implications for practice: The study provides a more comprehensive understanding of the experiences of clients, family and staff about the community life of people post‐ICMHS, providing insights and clearer directions for research and practice development.